Spatial Manipulation with Microfluidics - Lin, Benjamin; Levchenko, Andre (Frontiers in Bioengineering and Biotechnology, 2015)
Biochemical gradients convey information through space, time, and concentration, and are ultimately capable of spatially resolving distinct cellular phenotypes, such as differentiation, proliferation, and migration. How these gradients develop, evolve, and function during development, homeostasis, and various disease states is a subject of intense interest across a variety of disciplines. Microfluidic technologies have become essential tools for investigating gradient sensing in vitro due to their ability to precisely manipulate fluids on demand in well controlled environments at cellular length scales. This minireview will highlight their utility for studying gradient sensing along with relevant applications to biology.